Knowledge, Attitude, and Utilization of Artificial Intelligence among Nursing Professors: A Systematic Review - Cherry Ann Durante; Estrella San Juan (Future Science / FSH-PH Publications, 2026)
The use of artificial intelligence (AI) is one of the major disruptions in nursing education and research. This study aims to examine the knowledge, attitude, and utilization of AI among nursing professors. A systematic review of peer-reviewed research was conducted to identify the different factors that influence AI utilization among nursing educators. Based on the results of the study, even though professors express positive attitude towards AI use in the teaching and learning process, gaps in competence, ethical use, and institutional support in terms of access exist. Training, hands-on workshops, and guidelines on ethical use are proposed approaches that can strengthen the integration of AI in nursing education. This review concludes that curriculum revisions and AI integration can better prepare the nursing professors in the use of AI in hospital and community settings.